Comparison of Unguided De-Escalation Versus Guided Selection of Dual Antiplatelet Therapy After Acute Coronary Syndrome: A Systematic Review and Network Meta-Analysis. (28th July 2022) - Kuno, Toshiki; Fujisaki, Tomohiro; Shoji, Satoshi; Sahashi, Yuki; Tsugawa, Yusuke; Iwagami, Masao; Takagi, Hisato; Briasoulis, Alexandros; Deharo, Pierre; Cuisset, Thomas; Latib, Azeem; Kohsaka, Shun; et al.
Abstract : Background: The benefit of dual antiplatelet therapy (DAPT) for reducing ischemic events is greatest in the early period of acute coronary syndrome, and recent randomized controlled trials have investigated the unguided de-escalation strategy of changing potent P2Y12 inhibitors to less potent or reduced-dose P2Y12 inhibitors 1 month after acute coronary syndrome. However, it remains unclear which strategy is more effective and safer: the uniform unguided de-escalation strategy versus the personalized guided selection of DAPT with genotype or platelet function tests. Methods: PubMed, EMBASE, and Cochrane Central were searched for articles published from database inception to September 10, 2021. Randomized controlled trials investigating DAPT using clopidogrel, low-dose prasugrel, standard-dose prasugrel, ticagrelor, unguided de-escalation strategy, and guided selection strategy for patients with acute coronary syndrome were included. Hazard ratios and relative risk estimates were extracted from each study. The estimates were pooled using a random-effects network meta-analysis. The primary efficacy outcome was major adverse cardiovascular events, defined as a composite of cardiovascular death, myocardial infarction, or stroke. The primary safety outcome was major or minor bleeding. Secondary outcomes were all-cause death, cardiovascular death, myocardial infarction, stroke, stent thrombosis, and major bleeding. Results: This study included 19 randomized controlled trials with 69 746 patients. Compared with guided selection of DAPT, unguided de-escalation of DAPT was associated with a decreased risk of the primary safety outcome (hazard ratio, 0.48 [95% CI, 0.33–0.72]) without increased risks of major adverse cardiovascular events (hazard ratio, 0.82 [95% CI, 0.53–1.28]) or any secondary outcomes. The results were similar when the guided selection strategy was divided into platelet function–guided and genotype-guided strategies. Conclusions: Compared with guided selection of DAPT, unguided de-escalation of DAPT decreased bleeding without increasing ischemic events in patients after acute coronary syndrome. If a strategy of de-escalation is chosen, these findings do not support the routine use of personalized guiding tests. Registration: URL: https://www.crd.york.ac.uk/PROSPERO/ ; Unique identifier: CRD42021273082.